2021
DOI: 10.1002/jia2.25780
|View full text |Cite
|
Sign up to set email alerts
|

Global HIV mortality trends among children on antiretroviral treatment corrected for under‐reported deaths: an updated analysis of the International epidemiology Databases to Evaluate AIDS collaboration

Abstract: Introduction The Joint United Nations Programme on HIV/AIDS (UNAIDS) projections of paediatric HIV prevalence and deaths rely on the International epidemiology Databases to Evaluate AIDS (IeDEA) consortium for mortality estimates among children living with HIV (CHIV) receiving antiretroviral therapy (ART). Previous estimates, based on data through 2014, may no longer be accurate due to expanded paediatric HIV care and treatment eligibility, and the possibility of unreported deaths in CHIV consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
(44 reference statements)
2
2
0
Order By: Relevance
“…To the best of our knowledge, this is the first multicountry tracing study among CAYHIV considered LTFU. The high rates of unreported mortality are consistent with results from a systematic review, 4 and a multiregional tracing study, 16 although mortality in our study was lower than a Zambian tracing study in which 26% of children had died. 17 The children in the Zambian study were younger (0–15 years) compared with those in our study (0–24 years) and as reported, younger children have a higher risk of mortality compared with older children.…”
Section: Discussionsupporting
confidence: 90%
“…To the best of our knowledge, this is the first multicountry tracing study among CAYHIV considered LTFU. The high rates of unreported mortality are consistent with results from a systematic review, 4 and a multiregional tracing study, 16 although mortality in our study was lower than a Zambian tracing study in which 26% of children had died. 17 The children in the Zambian study were younger (0–15 years) compared with those in our study (0–24 years) and as reported, younger children have a higher risk of mortality compared with older children.…”
Section: Discussionsupporting
confidence: 90%
“…Although mortality was higher among CAYHIV reported as LTFU and traced compared with those retained [16, 17, 25–28], previous studies have reported even higher mortality estimates in those LTFU [1, 3, 29]. In rural Tanzania, 40% of adults living with HIV who were reported LTFU and traced, had died [27].…”
Section: Discussionmentioning
confidence: 99%
“…Among approximately 18 million persons living with HIV receiving ART through PEPFAR during October 2020-September 2022, prevalences of reported death were higher among children aged <5 years than among persons in older age groups, consistent with previously published findings (3). The additional finding that interruptions in treatment were also more common among children aged <5 years living with HIV might suggest that mortality is disproportionately underreported in this age group, because patients with interruptions in treatment or who are lost to follow-up might have died (3).…”
Section: Discussionmentioning
confidence: 99%